About Amos: Reading with Our Heart (Invited) - Lieblich, Amia (Narrative Works, 2014)
The proposed reading is guided by a deeply reflexive stance, seeing the entire “Amos” narrative as an expression of attempted escape from forgetfulness. Two introductory comments are made, about the problematic issues of analysis and of translation of narrative data. Utilizing the holistic-content reading, the piece was titled Decline, manifesting the foreclosed life story of an old, handicapped, and depressed man. From the standpoint of holistic-form reading, it was conceived as a thin story, typical of life narratives of the old. The divisions of past versus present and I versus we are proposed as analytic angles for reading the text. Special attention is paid to interruptions in the flow of the story, which may be seen as implicit meaningful messages to the listener-reader.